NK cell-based immunotherapy for malignant diseases - Cheng, Min; Chen, Yongyan; Xiao, Weihua; Sun, Rui; Tian, Zhigang (Cellular & molecular immunology, 2013)
Natural killer （NK） cells play critical roles in host immunity against cancer. In response, cancers develop mechanisms to escape NK cell attack or induce defective NK cells. Current NK cell-based cancer immunotherapy aims to overcome NK cell paralysis using several approaches. One approach uses expanded allogeneic NK cells, which are not inhibited by self histocompatibility antigens like autologous NK cells, for adoptive cellular immunotherapy. Another adoptive transfer approach uses stable allogeneic NK cell lines, which is more practical for quality control and large-scale production. A third approach is genetic modification of fresh NK cells or NK cell lines to highly express cytokines, Fc receptors and/or chimeric tumor-antigen receptors. Therapeutic NK cells can be derived from various sources, including peripheral or cord blood cells, stem cells or even induced pluripotent stem cells （iPSCs）, and a variety of stimulators can be used for large-scale production in laboratories or good manufacturing practice （GMP） facilities, including soluble growth factors, immobilized molecules or antibodies, and other cellular activators. A list of NK cell therapies to treat several types of cancer in clinical trials is reviewed here. Several different approaches to NK-based immunotherapy, such as tissue-specific NK cells, killer receptor-oriented NK cells and chemically treated NK cells, are discussed. A few new techniques or strategies to monitor NK cell therapy by non-invasive imaging, predetermine the efficiency of NK cell therapy by in vivo experiments and evaluate NK cell therapy approaches in clinical trials are also introduced.